Lack of effect of an in-line filter on cardiopulmonary exercise testing variables in healthy subjects - Abbasi, Asghar; Ahmad, Khadije; Ferguson, Carrie; Soriano, April; Calmelat, Robert; Rossiter, Harry B.; Casaburi, Richard; Stringer, William W.; Porszasz, Janos (European journal of applied physiology, 2024)
Purpose Pathogen transmission during cardio-pulmonary exercise testing (CPET) is caused by carrier aerosols generated during respiration. Methods Ten healthy volunteers (age range: 34 ± 15; 4 females) were recruited to see if the physiological reactions to ramp-incremental CPET on a cycle ergometer were affected using an in-line filter placed between the mouthpiece and the flow sensor. The tests were in random order with or without an in-line bacterial/viral spirometer filter. The work rate aligned, time interpolated 10 s bin data were compared throughout the exercise period. Results From rest to peak exercise, filter use increased only minute ventilation ( V ˙ E ) (Δ V ˙ E = 1.56 ± 0.70 L/min, P < 0.001) and tidal volume ( V T ) (Δ V T = 0.10 ± 0.11 L, P = 0.014). Over the entire test, the slope of the residuals for V ˙ CO 2 was positive (0.035 ± 0.041 (Δ L /L), P = 0.027). During a ramp-incremental CPET in healthy subjects, an in-line filter increased V ˙ E and V T but not metabolic rate. Conclusion In conclusion, using an in-line filter is feasible, does not affect appreciably the physiological variables, and may mitigate risk of aerosol dispersion during CPET.